Nano Fe3O4: A Novel and Magnetically Recyclable Catalyst for the Synthesis of 1,2,4,5-Tetrasubstituted Imidazoles in Solvent-Free Conditions - Montazeri, Naser; Pourshamsian, Khalil; Rezaei, Hamideh; Fouladi, Mahdi; Rahbar, Sasan (Asian Journal of Chemistry, 2013)
A convenient and efficient one-pot four-component synthesis of 1,2,4,5-tetrasubstituted imidazoles using nano Fe3O4 as magnetically recyclable catalyst is reported. The results show that the methodology has several advantages such as low loading of catalyst, excellent yield, short reaction time, operational simplicity and solvent-free conditions.